Bilateral Bundle Branch Area Pacing to Achieve Physiological Conduction System Activation. (August 2020) - Lin, Jinxuan; Chen, Keping; Dai, Yan; Sun, Qi; Li, Yuqiu; Jiang, Yong; Zhou, Yu'an; Chen, Ruohan; Jin, Yuanhao; Yan, Lirong; Zhou, Xiaohong; Cheng, Alan; et al.
Abstract : Background: Left bundle branch pacing (LBBP) is a technique for conduction system pacing, but it often results in right bundle branch block morphology on the ECG. This study was designed to assess simultaneous pacing of the left and right bundle branch areas to achieve more synchronous ventricular activation. Methods: In symptomatic bradycardia patients, the distal electrode of a bipolar pacing lead was placed at the left bundle branch area via a transventricular-septal approach. This was used to pace the left bundle branch area, while the ring electrode was used to pace the right bundle branch area. Bilateral bundle branch area pacing (BBBP) was achieved by stimulating the cathode and anode in various pacing configurations. QRS duration, delayed right ventricular activation time, left ventricular activation time, and interventricular conduction delay were measured. Pacing stability and short-term safety were assessed at 3-month follow-up. Results: BBBP was successfully performed in 22 of 36 patients. Compared with LBBP, BBBP resulted in greater shortening of QRS duration (109.3±7.1 versus 118.4±5.7 ms, P <0.001). LBBP resulted in a paced right bundle branch block configuration, with a delayed right ventricular activation time of 115.0±7.5 ms and interventricular conduction delay of 34.0±8.8 ms. BBBP fully resolved the right bundle branch block morphology in 18 patients. In the remaining 4 patients, BBBP partially corrected the right bundle branch block with delayed right ventricular activation time decreasing from 120.5±4.7 ms during LBBP to 106.1±4.2 ms during BBBP ( P =0.005). Conclusions: LBBP results in a relatively narrow QRS complex but with an interventricular activation delay. BBBP can diminish the delayed right ventricular activation, producing more physiological ventricular activation. Abstract : Supplemental Digital Content is available in the text.